Distortion of Government Policy Orientation in Public-Private Partnership (PPP) - Alexsander Yandra; Bunga Chintia Utami; Khuriyatul Husna (Indonesian Association for Public Administration, 2020)
This study examines the issue of Public-Private Partnership (PPP) policy discrepancies in reducing waste management and the occurrence of distortion of disagreement between the city’s government and the private sector in interpreting the contents and the scope of the policy inϐluenced by the interests of various stakeholders, the private sector and daily workers. This study uses a qualitative approach on the results of ethical and emic data, discussing the content of short-term project-oriented policies, which are limited to the transport of waste to cause long-term policy orientation anomalies in the trash business, thus impacting the accumulation of waste on the road, termination of unilateral contracts and demonstrations by daily workers. For this reason, PPP policy implementation shows high interest but has a low contribution to the community in Pekanbaru.